1990
DOI: 10.1200/jco.1990.8.7.1246
|View full text |Cite
|
Sign up to set email alerts
|

Imaging with indium111-labeled anticarcinoembryonic antigen monoclonal antibody ZCE-025 of recurrent colorectal or carcinoembryonic antigen-producing cancer in patients with rising serum carcinoembryonic antigen levels and occult metastases.

Abstract: We tested whether nuclear imaging with indium111 (111In)-labeled murine monoclonal (MoAb) anticarcinoembryonic antigen (anti-CEA) ZCE-025 antibody could detect recurrent disease in patients with a rising serum CEA level but negative findings for computed tomographic (CT) scans of the abdomen and pelvis, chest radiograph, and colonoscopy or barium enema. Twenty patients with a history of completely resected CEA-producing adenocarcinoma (18 with colon cancer, one with breast cancer, and one with Hodgkin's diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…In contrast, an 111 In-labeled antibody to colorectal cancer had excessive amounts of 111 In in the liver that frequently masked tumor targeting (Abdel-Nabi et al, 1987, 1990Lamki et al, 1990;Patt et al, 1990). In contrast to the monovalent chelateradiometal complex, Le Doussal et al (1989) found that a bivalent structure would be bound more stably at the tumor site, presumably because the divalent hapten-peptide could be crosslinked by two adjacent bsMAbs (Figure 2).…”
Section: Pretargeting As a New Paradigmmentioning
confidence: 99%
“…In contrast, an 111 In-labeled antibody to colorectal cancer had excessive amounts of 111 In in the liver that frequently masked tumor targeting (Abdel-Nabi et al, 1987, 1990Lamki et al, 1990;Patt et al, 1990). In contrast to the monovalent chelateradiometal complex, Le Doussal et al (1989) found that a bivalent structure would be bound more stably at the tumor site, presumably because the divalent hapten-peptide could be crosslinked by two adjacent bsMAbs (Figure 2).…”
Section: Pretargeting As a New Paradigmmentioning
confidence: 99%
“…Indeed, there are 4 different radioisotopes of iodine that can be used for nuclear imaging and therapy. Specifically, 123 I and 125 I are gamma emitters suitable for SPECT imaging, 124 I is a positronemitting isotope used for PET imaging, and 131 I emits both ÎČ and Îł rays and can thus be harnessed for both SPECT and radioimmunotherapy. Traditionally, the radioiodination of antibodies has been performed via the direct electrophilic radioiodination of tyrosine residues within the antibody to create radioiodotyrosines.…”
Section: The Isotopes Of Iodinementioning
confidence: 99%
“…120 However, the pre-or coinjection of unlabeled antibodies alongside 111 In-labeled mAbs has proven beneficial in other cases in which the target antigen is not shed. [121][122][123][124] In a different approach, Studer et al introduced a tetrapeptide linker (Ala-Leu-Ala-Leu) between the antibody and the chelator to promote the specific cleavage of the 111 In-chelator complex in the liver. 125 However, this approach led to very limited-if any-improvements in the activity concentrations retained in the liver of mice.…”
Section: Indium-111mentioning
confidence: 99%
“…For example, 111 In-labeled ZCE-025 (an anti-CEA mAb that does not react with normal granulocyte glycoproteins) was investigated in several studies for the detection of primary, metastatic, or recurrent colorectal carcinomas (Abdel-Nabi et al 1988; Abdel-Nabi et al 1991; Kramer et al 1988; Patt et al 1988; Patt et al 1990). Imaging in patients with rising CEA levels successfully detected metastatic colorectal cancer that could not be detected by other methods, therefore changing patient management in many cases.…”
Section: Spect and Gamma Camera Imagingmentioning
confidence: 99%